Pemilu Serentak Tahun 2024: Prediksi Partisipasi Politik Masyarakat Mengacu Pada Perbandingan Anggaran Kampanye Pemilu Serentak Tahun 2019 - Arlen Intani (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Simultaneous election in 2019 succeed increasing highly political participation. Compared with the previous election, the participation rate in 2019 election implies significantly enhancement from 69,6% (2014 election) become 81,9% (2019 election). Based on this study, the result found that parties in 2019 election afford huge funds for campaign could increase participation from public instead of other parties. The prediction of possibility which will occur in 2024 simultaneous election regarding public relate to the funds enhancement that can be increased by 88,6%. This study uses a qualitative method by grounded theory approach. The aim of this study is predicting how the election participation will increasing regarding the huge funds that state afford compared to the previous years. Subjects of this study is public as a participant, politic parties behavior, and campaign funds regulation. Data collection gained by observing various data from different resources which from news pages, related journal, and government regulation it selves. Data analysis in qualitative research will be simultaneously held with other part of this qualitative research development from data and findings writing. The analysis step combine between description and regression analysis.